Climbing Speed and Acclimatization are determinants of Acute Mountain Sickness on Mount Sumbing, Indonesia - M. Shoffiul Awal; Moh. Ubaidillah Faqih; Karyo; Tiara Putri Ryandini (Jurnal Keperawatan Olahraga, 2026)
Background: Acute Mountain Sickness (AMS) commonly affects individuals ascending above 2,500 meters due to inadequate adaptation to hypobaric hypoxia. Climbing speed and acclimatization are important modifiable risk factors, although evidence regarding their contribution among Indonesian mountain climbers remains limited. Aims:  To investigate the relationships between climbing speed, acclimatization, and the incidence of acute mountain sickness among climbers of Mount Sumbing, Wonosobo Regency, Central Java. Methods: A quantitative study with a correlational cross-sectional design was conducted among 109 Mount Sumbing climbers recruited using a consecutive sampling technique. Climbing speed was assessed based on ascent performance, acclimatization status was evaluated using predefined acclimatization criteria, and acute mountain sickness was measured using the Lake Louise Acute Mountain Sickness Score (LLAMS). Spearman's rank correlation test was performed to examine the relationships between variables, with statistical significance set at α = 0.05. Results: Significant positive correlations were identified between both independent variables and the incidence of acute mountain sickness. Climbing speed demonstrated a moderate positive correlation with AMS (p < 0.001; r = 0.444), indicating that faster ascent was associated with a greater likelihood of developing AMS. Acclimatization also showed a statistically significant positive correlation with AMS (p < 0.001; r = 0.874), suggesting that inadequate acclimatization substantially increased the risk of acute mountain sickness. Among the two variables, acclimatization exhibited the strongest association with AMS. Conclusions: Climbing speed and acclimatization significantly influence acute mountain sickness among Mount Sumbing climbers. Appropriate ascent pacing and adequate acclimatization are essential to reduce AMS risk and support preventive guidelines and climber safety education.